LARYNX DISEASES - Yu.L. Soldatskiy (Union of pediatricians of Russia, 2007)
The lecture describes one of the most frequent larynx diseases - stenosis both congenital and acquired forms. The author highlights the aetiology of this pathology and ways to treat it.Key words: laryngostenosis, congenital stenosis, acquired stenosis, tracheotomy, children.